The Opinions of Foreign Tourist Towards Development for Bangkok to be the Tourism Center of Greater Mekong Sub-Region Railways - Kieanwatana, Komsit; Yongjian, Pu (Academic Journal of Thailand National Sports University, 2022)
The purpose of this study was to study the opinions of foreign tourist towards development for Bangkok to be the tourism center of Greater Mekong Sub-region railways. The questionnaires were administered as a survey tool and the data were analyzed statistically using means, and standard deviation. The following results were: The overall opinions of foreign tourist towards Bangkok development for to be the tourism center of Greater Mekong Sub-region Railways were at high level (x = 3.730). The most significant issue was Tourism Marketing Mix (t = 3.791) followed by Components of Tourism Resources (X = 3.785), Tourism Business (t = 3.716), Private Management (X = 3.704), and Public Administration (X = 3.656) respectively.